Estimación dinámica de una estructura de tasas de interés para Colombia: análisis empírico con filtros de Kalman (2012)
In Colombia the o ficial estimation for the term structure model is given by [6] development which is widely accepted and used. This estimation is based on the curve tting with available data, only for one day ahead, making di cult to estimate the future zero-coupon curve. Taking into account the importance of having an estimation of the term structure for the valuation of nancial assets in the Colombian market, this research proposes a methodology to estimate in dynamic form the parameters of interest rates in the Nelson and Siegel Model. This required the use of the re-parameterization proposed by [3], which determines the shape of the term structure through latent factors level, slope and curvature. This paper proposes dynamic estimation of the term structure of interest rate using a Kalman fi lter methodology throughout the state - space framework. Results show us that predicts are successful for more than one period in the future.